2014
DOI: 10.1039/c3nr06694k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PEGylated low generation dendrimer-entrapped gold nanoparticles for CT imaging applications

Abstract: Dendrimer-entrapped gold nanoparticles (Au DENPs) can be formed using low-generation dendrimers pre-modified by polyethylene glycol (PEG). The formed PEGylated Au DENPs with desirable stability, cytocompatibility, and X-ray attenuation properties enable efficient computed tomography imaging of the heart and tumor model of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 49 publications
(65 reference statements)
6
56
0
Order By: Relevance
“…Further, through the PEGylation chemistry, targeting ligands of folate [66] or lactobionic acid [67] can be linked onto the surface of Au-DENPs through the PEG spacer for targeted CT imaging of FRexpressing KB tumor and human hepatocellular carcinoma tumor, respectively. To avoid the use of expensive high generation PAMAM dendrimers, low-generation dendrimers (e.g., G2) can also be modified with PEG for effective entrapment of Au nanoparticles with a size of 1-2 nm for tumor CT imaging applications [68,69]. Alternatively, dendrimer-stabilized Au nanoparticles (Au DSNPs) can be prepared using G2 PAMAM dendrimers as a stabilizer under a hydrothermal condition without additional reducing agents for animal organ [70] and tumor [71] CT imaging.…”
Section: Reviewsmentioning
confidence: 99%
“…Further, through the PEGylation chemistry, targeting ligands of folate [66] or lactobionic acid [67] can be linked onto the surface of Au-DENPs through the PEG spacer for targeted CT imaging of FRexpressing KB tumor and human hepatocellular carcinoma tumor, respectively. To avoid the use of expensive high generation PAMAM dendrimers, low-generation dendrimers (e.g., G2) can also be modified with PEG for effective entrapment of Au nanoparticles with a size of 1-2 nm for tumor CT imaging applications [68,69]. Alternatively, dendrimer-stabilized Au nanoparticles (Au DSNPs) can be prepared using G2 PAMAM dendrimers as a stabilizer under a hydrothermal condition without additional reducing agents for animal organ [70] and tumor [71] CT imaging.…”
Section: Reviewsmentioning
confidence: 99%
“…The particles were found to accumulate in tumor and the bladder, although much higher CT attenuation was observed in the latter. In a comparison to Omnipaque, formulated particles remained in the bladder for longer time periods [96].…”
Section: Passively Targeted Gold Nanoparticle Formulationsmentioning
confidence: 99%
“…In the early days, dendrimers were only used as vectors of some imaging elements; for example, Mn(II) or Gd(III) chelating dendrimers were prepared as contrast agents for MRI applications; 88,91,94 dye-conjugated dendrimers were used for fluorescence imaging; 95,96 and dendrimer-entrapped Au nanoparticles (Au DENPs) or iodinated-compounds conjugated dendrimers were applied to CT. [97][98][99][100] With multi-signal elements and targeting molecules in one dendrimer molecule, dendrimers can easily target to the intended imagining organs. Dendrimers conjugated with folic acid (FA) and Cu 2+ were studied as bioprobes to target and image human cancers using synchrotron X-ray fluorescence analysis, and the results showed that the targeting probes increased the intensity of fluorescence signal compared to 93 Likewise, folate receptor-targeted dendrimer nanoclusters (DNCs) labeled with Gd can be used for MRI of cancers with high expression of folate-receptor.…”
Section: Dendrimers As Imaging Agentsmentioning
confidence: 99%